P.024 Long-term use of patisiran in patients with hereditary transthyretin amyloidosis (hATTR): 12 month efficacy & safety data from a global open label extension (OLE) study. (June 2019) - Gonzalez-Duarte, A; Coelho, T; Adams, D; Yang, C; Polydefkis, M; Kristen, A; Tournev, I; Schmidt, H; Berk, J; Lin, K; Gandhi, PJ; Sweetser, M; et al.
Abstract : Background: Hereditary transthyretin-mediated (hATTR) amyloidosis is a multi-systemic, heterogenous, life-threatening disease. Patisiran resulted in significant improvement in neuropathy and QoL at 18-months compared to placebo, and was generally well-tolerated in the Phase 3 APOLLO study. Methods: Multi-center, OLE study to evaluate the efficacy and safety of long-term patisiran dosing for ≤ 5 years in hATTR amyloidosis patients with polyneuropathy who have completed the APOLLO study (NCT02510261). Endpoints include safety, tolerability and long-term efficacy of patisiran. Measures of clinical benefit are the same endpoints used in APOLLO including changes in mNIS+7 composite neuropathy impairment score and QoL (Norfolk QoL-DN) Results: As of December 2017, 184 of 186 (99%) patients who completed APOLLO and 25 patients from the Ph 2 OLE study enrolled in the Global OLE study. Baseline data for 211(APOLLO/placebo, n=49; APOLLO/patisiran, n=137 and patisiran Ph 2 OLE, n=25) patients included: median age 61 years (26-84); 74% males; 46% V30M. Interim safety data and 12-month efficacy results will be presented. Conclusions: The global OLE study includes a diverse population of hATTR amyloidosis patients. Interim data will include the long-term safety and maintenance of effect in patients continuing on patisiran, as well as the impact of treatment with patisiran on patients previously treated with placebo.